Interfaces and mechanical properties of recycled rubber–polyethylene terephthalate–wood composites. (March 2014) - Cosnita, Mihaela; Cazan, Cristina; Duta, Anca
Rubber-thermoplastic-based composites represent widely used materials due to their good mechanical properties that can be controlled according to the composition and interfaces. Considering the mechanical properties as output, recycled polyethylene terephthalate-rubber-based composites with optimized curing temperature were obtained, where rubber acts as a matrix, polyethylene terephthalate as filler and high-density polyethylene as compatibility agent. By adding another recycled material wood (sawdust), a novel composite with tailored properties was obtained via compression molding. The composites were mechanically tested in terms of compression and tensile strength. The optimized compositions were investigated by X-ray diffraction and further characterization was done to outline the interfaces contribution: surface/interface topology (atomic force microscopy) and bonding (Fourier transform infrared); contact angle measurements were developed, to evaluate the surface energy as a tool for estimating possible (thermal) degradation. Water stability was investigated and its plasticizer role was outlined. Wood sawdust addition at recycled rubber–polyethylene terephthalate–high-density polyethylene composites had a remarkable effect on the mechanical properties, recommending this composite type as structural material.